Glycosylation Profile of Immunoglobulin G Is Cross-Sectionally Associated With Cardiovascular Disease Risk Score and Subclinical Atherosclerosis in Two Independent Cohorts. Issue 11 (25th May 2018) - Menni, Cristina; Gudelj, Ivan; Macdonald-Dunlop, Erin; Mangino, Massimo; Zierer, Jonas; Bešić, Erim; Joshi, Peter K.; Trbojević-Akmačić, Irena; Chowienczyk, Phil J.; Spector, Tim D.; Wilson, James F.; Lauc, Gordan; et al.
Abstract : Rationale: : One measure of protein glycosylation (GlycA) has been reported to predict higher cardiovascular risk by reflecting inflammatory pathways. Objective: : The main objective of this study is to assess the role of a comprehensive panel of IgG glycosylation traits on traditional risk factors for cardiovascular disease and on presence of subclinical atherosclerosis in addition to GlycA. Methods and Results: : We measured 76 IgG glycosylation traits in 2970 women (age range, 40–79 years) from the TwinsUK cohort and correlated it to their estimated 10-year atherosclerotic cardiovascular disease risk score and their carotid and femoral plaque measured by ultrasound imaging. Eight IgG glycan traits are associated with the 10-year atherosclerotic cardiovascular disease risk score after adjusting for multiple tests and for individual risk factors—5 with increased risk and 3 with decreased risk. These glycans replicated in 967 women from ORCADES cohort (Orkney Complex Disease Study), and 6 of them were also associated in 845 men. A linear combination of IgG glycans and GlycA is also associated with presence of carotid (odds ratio, 1.55; 95% confidence interval, 1.25–1.93; P =7.5×10 -5 ) and femoral (odds ratio, 1.32; 95% confidence interval, 1.06–1.64; P =0.01) plaque in a subset of women with atherosclerosis data after adjustment for traditional risk factors. One specific glycosylation trait, GP18-the percentage of FA2BG2S1 glycan in total IgG glycans, was negatively correlated with very-low-density lipoprotein and triglyceride levels in serum and with presence of carotid plaque (odds ratio, 0.60; 95% confidence interval, 0.50–0.71; P =5×10 -4 ). Conclusions: : We find molecular pathways linking IgG to arterial lesion formation. Glycosylation traits are independently associated with subclinical atherosclerosis. One specific trait related to the sialylated N-glycan is negatively correlated with cardiovascular disease risk, very-low-density lipoprotein and triglyceride serum levels, and presence of carotid plaque. Abstract : Supplemental Digital Content is available in the text.